Education and Society in the Caribbean: Jamaican Educational Research; A Summary and Commentary - Hamilton, Marlene A. (Faculty of Education, University of the West Indies, 1989)
The paper reviews educational research, mainly in the formal system, during the 1970s and 1980s in Jamaica, which provides information on access to education, educational achievement and socialization.
Keywords: Access to Education